2013
DOI: 10.1371/journal.pone.0060245
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 p24gag Derived Conserved Element DNA Vaccine Increases the Breadth of Immune Response in Mice

Abstract: Viral diversity is considered a major impediment to the development of an effective HIV-1 vaccine. Despite this diversity, certain protein segments are nearly invariant across the known HIV-1 Group M sequences. We developed immunogens based on the highly conserved elements from the p24gag region according to two principles: the immunogen must (i) include strictly conserved elements of the virus that cannot mutate readily, and (ii) exclude both HIV regions capable of mutating without limiting virus viability, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(88 citation statements)
references
References 76 publications
4
82
0
2
Order By: Relevance
“…In agreement with previous results, 20 , 21 , 76 , 77 priming with CE DNA was more efficient at inducing CE-specific T cell responses in the blood than immunization with the FL vaccine, for both Gag and Env. Gag CE-specific responses were also found in rectal mucosa lymphocytes (Env responses were not evaluated in the rectal mucosa due to sample limitations).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with previous results, 20 , 21 , 76 , 77 priming with CE DNA was more efficient at inducing CE-specific T cell responses in the blood than immunization with the FL vaccine, for both Gag and Env. Gag CE-specific responses were also found in rectal mucosa lymphocytes (Env responses were not evaluated in the rectal mucosa due to sample limitations).…”
Section: Discussionsupporting
confidence: 92%
“…We previously reported the generation of two DNA vaccines targeting the highly conserved sequences in HIV Gag 20 , 21 , 73 (and its homolog SIV p27CE) 76 and in HIV Env (Env CE) 77 ( Figure 1 A) and demonstrated induction of robust CE-specific T cell responses in cohorts of vaccinated macaques. The CE selection included analysis of MHC binding prediction to address immunogenicity in humans, and we found that epitopes from all MHC class I known supertypes were represented in Gag CE.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To address the problem of viral variability, many approaches have been tested including strategies that use consensus, center-of-tree or ancestral sequences, multiple strains or mosaic immunogens, immunogens consisting of known epitopes, and chimeric molecules expressing a selection of the most conserved epitopes from different clades of HIV . In our approach (20)(21)(22), we designed a plasmid DNA (pDNA) vaccine to focus the immune response to conserved elements (CE) of the HIV-1 proteome based on stringent conservation, broad HLA-coverage, and association with HIV control (19,(23)(24)(25). The p24…”
mentioning
confidence: 99%